STUDY OF THE EFFECT OF A NEW COMBINED INHIBITOR AND A PERMANENT MAGNETIC FIELD ON CORROSION AND SALT DEPOSITION - K.A.Mammedov (Academic Scientific Journal of Chemistry, 2020)
This academic article encompasses the investigation results concerning, the composite acquired from the mixture of hydrated technical phosphatide, cubic thickness of polypropylene glycol, and sodium hexametaphosphate. According to the outcomes of laboratory researches, it was determined that the developed new composite provides not only prevention of equipment from corrosion, but also protection of those from salt deposition. Furthermore, as a result of the joint effect of a stable magnetic field of 280 kA/m, high protective efficiency was determined. Thus, the optimum consumption was found to be 150 mg/l. In this case, the protection effectiveness against corrosion and salt deposition accounted for 93% and 85% accordingly. Commercial tests of the combined action of the reagent and the permanent magnetic field were carried out on the cooling system of compressors “Bibiheybatneft” OGED (Oil and Gas Extraction Department). In the field with the combined use of a magnetic field and inhibitors the protective effect is 90%, and the protective effect of salt deposition is 73%